Vanishing Echoes - Vorreiter, Victoria (Journal of Urban Culture Research, 2014)
Experts agree that with the rush to globalization, half of the world’s 6,900 languages will disappear within the next fifty years, and with them will vanish the ideas, history, culture, stories, and songs that these languages embody. This loss is felt not only by the community that has practiced ancestral traditions throughout the millennia, but also by mankind, for cultural diversity provides a source of exchange, innovation and creativity that is vital to the survival of humankind. For the ancient civilizations of mainland Southeast Asia rooted in oral tradition, music is a primary portal to understanding the world. As these smaller communities become assimilated into the dominant political and economic powers in this new age, may action be taken to preserve their arts, songs and ceremonies in recognition of the multiplicity that once was ours.